Cultural and social aspects of animal domestication in Greek traditional society - ECONOMOU (Α. ΟΙΚΟΝΟΜΟΥ), A. (Journal of the Hellenic Veterinary Medical Society, 2017)
The study of the ways, perceptions and practices by means of which a traditional society domesticates animals constitutes an important chapter in the understanding and interpretation of the making of its civilization, as the presence of animals can be found in all its facets and expressions. In the present paper which, in its initial form, was delivered as a lecture to the Hellenic Veterinary Medical Society, reference was made to the ways the Greek traditional society uses to integrate animals in its cultural system. This reference, however, was a brief and indicative one, as these ways have not been sufficiently studied from a folkanthropological point of view in Greece. This integration happened in many different ways, through the production and reproduction of the animals in their quality as financial asset, the consumption of their meat during week days and celebrations, their naming, the care to prevent and to cure illnesses affecting them, their participation in the worship rituals of saints as sacrificial offers, both real and symbolic, their position in the symbolic and the imaginary as it is depicted in oral narrative (legends, fairy tales, traditions, proverbs). Special mention is made to the saint patrons (St. Modestos, St. Mamas, St. Minas) of the animals in orthodox Christian religion and in Greek popular beliefs and practices.